(untitled) - Hertling, Claus (Cambridge, 2002)
For those working in singularity theory or other areas of complex geometry, this volume will open the door to the study of Frobenius manifolds. In the first part Hertling explains the theory of manifolds with a multiplication on the tangent bundle. He then presents a simplified explanation of the role of Frobenius manifolds in singularity theory along with all the necessary tools and several applications. Readers will benefit from this careful and sound study of the fundamental structures and results in this exciting branch of mathematics.
Keywords: Singularities (Mathematics),Frobenius algebras,Moduli theory,Miền cá biệt ( toán ),Frobenius đại số,Lý thuyết Moduli